(untitled) (Baghdad Science Journal, 2012)
The aqueous extract of Citrullius colocynthis dried seeds (160 ?g/ml) was in vitro evaluated for its effect on phagocytic index (PI) and lymphocyte transformation index (LTI) of blood cells obtained from 30 apparently healthy blood donors (15 males and 15 females). The PI was further in vivo evaluated in cells of peritone, spleen and liver of mice treated with the extract at a dose of 0.64 mg/kg. The results revealed that in in vitro study, phagocytic cells treated with the extract showed a significant increased percentage as compared with untreated cells (60.0 vs. 44.1%). Phagocytes obtained from peritone (44.1 vs. 30.0%) and spleen (45.6 vs. 39.6 %) of treated and untreated mice behaved in a similar manner, while liver phagocytes showed no significant difference between PI of immunological function of the investigated cells, and may use as therapeutic agent. treated and untreated mice. For LTI, cultures I and II shared an approximated mean (70.0 and 68.0%, respectively), but both indices were significantly higher than the recorded LTI in culture III (54.0%). These findings suggest that the plant extract is effective in enhancing the